The judgmental failures of the Western European states towards the Russian Federation by perceiving it through European values. - Chabska Katarzyna (2022)
The purpose of this article is to show the Western European judgmental failures towards Russia by perceiving it through European values. These failures have a negative impact on European security and all of them appeared because Russia was considered the European state and the European values were put in Russia. In fact, the Russian Federation is only a geographic part of Europe, but no longer a part of European civilization.